Branding of the Sangga Braja Community in soft marketing and cultural education in the new normal era - Shannaz Mutiara Deniar; Yeyen Pratika (Community Empowerment, 2022)
The objective of this community service is to assist and preserve Batu City's artistic and cultural products. The partner is the Sangga Braja Community, which is particularly concerned in preserving Batu City's arts and culture and already has some basic facilities, but there are issues with branding, public education, and human resources. The aim of this program is to maintain Batu City's artistic and cultural assets so that they can be utilized to their full potential. To address these issues, this service method will emphasize mentoring and training, primarily related to the use of social media as a promotional and educational tool, as well as efficiency and effectiveness in community management, in the form of cultural branding workshops, manufacturing training, social media content, use of social media, photography training, and institutional management. The program's outcomes include soft skills training and social media usage guidelines. The community's eagerness for engaging in numerous current activities ensured that the training and mentorship went smoothly.